293 PRE-ADMISSION POTENTIALLY INAPPROPRIATE PRESCRIBING PREVALENCE ON A CARE OF THE OLDER ADULT MEDICAL WARD. (25th October 2022) - Cosgrave, N; Stankard, A; Walsh, J; Walsh, S; Mulroy, M; Mason, C
Abstract: Background: Potentially Inappropriate Prescribing (PIP) is a common but critical issue in care of the older adult. It is estimated that between 50 and 70% of those over 65 years are receiving at least one potentially inappropriate medication. Polypharmacy is a good indicator of PIP as it can indicate over- and inappropriate prescribing through prescribing cascade, exposing patients to risks of drug interactions and Adverse Drug Events (ADEs). 10-20% of hospital admissions of older adults are directly related to ADE of inappropriately prescribed drugs. Methods: Point prevalence study using the 'Screening Tool of Older Persons Prescriptions' (STOPP) to identify PIPs on a geriatric medicine ward. Patients over 65 years of age admitted from home were included in the study. Patients' pre-admission medications and changes made to these were assessed using STOPP. Results: Sixteen patients out of 22 met the inclusion criteria. The average age of the patients included in the study was 82.3 years with a range from 70 to 88 years. 75% were female. 94% had polypharmacy prior to admission with an average of 2.25 PIPs (range 0 to 5). 43% (n=7) had all their PIPs addressed by a geriatrician as per STOPP, with a further 18% (n=3) having some of their PIPs altered. 25% (n=4) did not have any alterations to their PIPs. Conclusion: Despite widely known impacts of PIPs on older adults, PIP remains highly prevalent in those admitted to hospital. PIP and polypharmacy can increase incident frailty two-fold and polypharmacy and frailty can lead to a 6-fold increase in mortality within two and a half years. We must actively educate all those involved in prescribing for this cohort of patients to reduce PIPs and their adverse effects.